Napping Affects Night-Shift Nurses' Occupational Safety - Anika Kartika; Krisna Yetti; Tuti Afriani; Hanny Handiyani; Dyah Fitri Wulandari (Indonesian Journal of Global Health Research, 2026)
Napping is an evidence-based method used to reduce fatigue and increase alertness during night shift work. Objective: This study aims to identify the relationship between napping in night shift nurses and the work safety of nurses in hospitals. Method of This research uses a quantitative research design using a cross sectional method. Data was collected from 213 nurses using the Napping Nurse Questionnaire and the Occupational Safety questionnaire. Data collection was carried out from June to December 2024. Data analysis included univariate analysis in the form of a frequency distribution table, bivariate analysis using the chi-square test, and multivariate analysis using the multiple logistic regression test (p>0.05). Results There is a significant relationship between the implementation of night shift nurse napping and work safety at Khidmat Sehat Afiat Regional Hospital, Depok City and Graha Permata Ibu Hospital (p=0.001). Nurses with good napping will have the opportunity to have good work safety. The implementation of napping is the factor that most influences nurses' work safety.